Prevalence and implications of frailty in acute stroke: systematic review & meta-analysis. (29th March 2022) - Burton, Jennifer K; Stewart, Jennifer; Blair, Mairi; Oxley, Sinead; Wass, Amy; Taylor-Rowan, Martin; Quinn, Terence J
Abstract: Background: frailty is common in older adults and associated with poor outcomes following illness. Although stroke is predominantly a disease of older people, our knowledge of frailty in stroke is limited. We aimed to collate the literature on acute stroke and frailty to estimate the prevalence of pre-stroke frailty and its associations with outcomes. Methods: paired researchers searched multidisciplinary electronic databases for papers describing frailty and acute stroke. We assessed risk of bias using Newcastle-Ottawa tools appropriate to study design. We created summary estimates of pre-stroke frailty using random effects models. We collated whether studies reported significant positive associations between frailty and clinical outcomes in adjusted models. Results: we included 14 studies ( n  = 27, 210 participants). Seven studies ( n  = 8, 840) used a frailty index approach, four studies ( n  = 14, 924) used Hospital Frailty Risk Scores. Pooled prevalence of pre-stroke frailty was 24.6% (95% confidence interval, CI: 16.2–33.1%; low quality evidence, downgraded due to heterogeneity, bias). Combining frailty and pre-frailty (nine studies, n  = 23, 827), prevalence of any frailty syndrome was 66.8% (95%CI: 49.9–83.7%). Seven studies were at risk of bias, from participant selection or method of frailty assessment. Pre-stroke frailty was associated with all adverse outcomes assessed, including longer-term mortality (positive association in 6 of 6 studies reporting this outcome; odds ratio: 3.75 [95%CI: 2.41–5.70]), length of admission (3 of 4 studies) and disability (4 of 6 studies). Conclusions: despite substantial heterogeneity, whichever way it is measured, frailty is common in patients presenting with acute stroke and associated with poor outcomes. This has implications for the design of stroke services and pathways. Video Abstract: